Impact of Positive Reinforcement Theory on Weightlifter’s Performance - Saqib Fayyaz; Sabahat Afsheen; Adeel Khan (The Sky)
A common problem was observed at local level weightlifting clubs in Lahore, Pakistan i.e., coaches use inappropriate ways (shouting and abusing) to get desired performance results but, it ends in young weightlifter’s resentment and take them away from their sport targets and some choose to quit weightlifting sport as well. The existing literature about acquiring desired results in sports suggests; only positive approach can be useful i.e., Positive Reinforcement Theory ‘PRT’ developed by B F Skinner (Marzieh Gordan, 2014). Hence, in this applied deductive type quantitative study, an eight-week experiment was conducted in Lahore which tested the implications of Positive Reinforcement Theory on young weightlifters’ performance. The objectives of this study were; (a) to apply Positive Reinforcement Theory in weightlifting sport to examine the cause-and-effect relationship between positive reinforcement and young weightlifter’s performance, (b) to test if the study’s Positive Reinforcement Program ‘PRP’ model helps young weightlifters to achieve desired targets within given timeframe or not? At first, pre-competition was administered to record standard performance results of both groups. Secondly, ‘PRP’ Model based on ‘PRT’ was introduced to experimental group and then post-competition testing was conducted to record and compare performance results of both groups. The results of both groups’ Paired Sample t-test and Independent Sample t-test, using statistical package SPSS version 23, showed a significant impact of ‘PRP’ model on the young weightlifter’s performance. Therefore, it is concluded that; acquisition of young weightlifters’ desired performance results. Coaches should use ‘PRP’ model rather than applying inappropriate ways to motivate young weightlifters. The PRP model also helps young weightlifters to achieve their targeted performance results within given timeframe.